Manufacturing operation transfer from USA to Mexico Case study - Vargas-Hernández, José G. (2017)
Companies are continuously looking for resources and skills which lead them to a higher performance. Companies should manage not only the resource access, but a collaborative strategy as well, which maximizes the benefits of a healthy and constructive interaction expected between customer and provider. This paper analyzes the case of a company accustomed to operate with a traditional business model, and the paradigm shift that was necessary as a result of its exposure to the new customer’s requirements and demands for total openness, cooperation and transparency.